“It’s so Cute I Could Crush It!”: Understanding Neural Mechanisms of Cute Aggression - Stavropoulos, Katherine K. M.; Alba, Laura A. (Frontiers in Behavioral Neuroscience, 2018)
Abstract The urge people get to squeeze or bite cute things, albeit without desire to cause harm, is known as “cute aggression”. Using electrophysiology (ERP), we measured components related to emotional salience and reward processing. Participants aged 18-40 years (n = 54) saw four sets of images: cute babies, less cute babies, cute (baby) animals, and less cute (adult) animals. On measures of cute aggression, feeling overwhelmed by positive emotions, approachability, appraisal of cuteness, and feelings of caretaking, participants rated more cute animals significantly higher than less cute animals. There were significant correlations between participants’ self-report of behaviors related to cute aggression and ratings of cute aggression in the current study. N200. A significant effect of “cuteness” was observed for animals such that a larger N200 was elicited after more versus less cute animals. A significant correlation between N200 amplitude and the tendency to express positive emotions in a dimorphous manner (e.g. crying when happy) was observed. RewP. For animals and babies separately, we subtracted the less cute condition from the more cute condition. A significant correlation was observed between RewP amplitude to cute animals and ratings of cute aggression towards cute animals. RewP amplitude was used in mediation models. Mediation Models. Using PROCESS (Hayes, 2013), mediation models were run. For both animals and babies, the relationship between appraisal and cute aggression was significantly mediated by feeling overwhelmed. For cute animals, the relationship between N200 amplitude and cute aggression was significantly mediated by feeling overwhelmed. For cute animals, there was significant serial mediation for RewP amplitude through caretaking, to feeling overwhelmed, to cute aggression, and RewP amplitude through appraisal, to feeling overwhelmed, to cute aggression. Our results indicate that feelings of cute aggression relate to feeling overwhelmed and feelings of caretaking. In terms of neural mechanisms, cute aggression is related to both reward processing and emotional salience.